Cross-linked α-l-rhamnosidase aggregates with potential application in food industry - Alvarenga, Adriana Elizabet (2014)
α-l-Rhamnosidase (E.C. 3.2.1.40) from Brevundimonas sp. Ci19 was immobilized as a cross-linked enzyme aggregate (CLEA) via precipitation with acetone followed by glutaraldehyde cross-linking. The effects of precipitation and cross-linking on CLEA activity were investigated and characterized. Sixty percent acetone solution and 2.0 % glutaraldehyde were used at pH 7.0 for 1-h cross-linking reaction. The yield of rhamnosidase-CLEA was approximately 80 % starting from crude extracts or pure enzyme suggesting non-purification steps are required for extended use. No significant differences in optimum pH and temperature values of the enzyme were recorded after immobilization. The rham-CLEA recycled 4 times showed about 80 % rhamnosidase activity; meanwhile, in the fifth and six recycled time, the enzyme activity was reduced to about 40 and 20 %, respectively.